The social play record : a toolkit for assessing and developing social play from infancy to adolescence - White, Chris, 1953- (JKP resource materials., 2006)
Social play is about relating to others, playing and making friends - all of which are key elements for social inclusion, adjustment and well-being. The Social Play Record is a practical resource for assessing and developing social play in children with autistic spectrum disorders (ASDs) or difficulties with social interaction. This toolkit is designed to be used collaboratively with children, parents, carers and practitioners. It is suitable for assessing children of all learning abilities and stages of development, from early infancy to adolescence, and includes photocopiable assessmen.